Web-based visualization tools for bacterial genome alignments - Florea, Liliana (Oxford University Press, 2000)
With the increase in the flow of sequence data, both in contigs and whole genomes, visual aids for comparison and analysis studies are becoming imperative. We describe three web-based tools for visualizing alignments of bacterial genomes. The first, called Enteric, produces a graphical, hypertext view of pairwise alignments between a reference genome and sequences from each of several related organisms, covering 20 kb around a user-specified position. Insertions, deletions and rearrangements relative to the reference genome are color-coded, which reveals many intriguing differences among genomes. The second, Menteric, computes and displays nucleotide-level multiple alignments of the same sequences, together with annotations of ORFs and regulatory sites, in a 1 kb region surrounding a given address. The third, a Java-based viewer called Maj, combines some features of the previous tools, and adds a zoom-in mechanism. We compare the Escherichia coli K-12 genome with the partially sequenced genomes of Klebsiella pneumoniae, Yersinia pestis, Vibrio cholerae, and the Salmonella enterica serovars Typhimurium, Typhi and Paratyphi A. Examination of the pairwise and multiple alignments in a region allows one to draw inferences about regulatory patterns and functional assignments. For example, these tools revealed that rffH, a gene involved in enterobacterial common antigen (ECA) biosynthesis, is partly deleted in one of the genomes. We used PCR to show that this deletion occurs sporadically in some strains of some serovars of S.enterica subspecies I but not in any strains tested from six other subspecies. The resulting cell surface diversity may be associated with selection by the host immune response.